Kinerja Keuangan, Opini Audit, dan Tingkat Korupsi Pemerintah Provinsi di Indonesia: Bukti Empiris Periode 2018-2023: Indonesia - Dewi Ardika; Afni Sirait (Owner : Riset dan Jurnal Akuntansi, 2026)
This study examines the relationship between financial performance, audit opinions, and corruption levels in Indonesian provincial governments during the period 2018–2023. Financial performance is proxied by efficiency, effectiveness, fiscal independence, and fiscal dependency ratios, while audit opinions are measured based on opinions issued by the Badan Pemeriksa Keuangan (BPK). Corruption is measured using the number of corruption cases reported by Indonesia Corruption Watch (ICW). Using panel data from ten provinces with the highest corruption cases and applying multiple linear regression analysis, the results show that fiscal dependency has a significant effect on corruption levels, whereas efficiency, effectiveness, fiscal independence, and audit opinions do not exhibit significant individual effects. Nevertheless, the variables jointly explain variations in corruption levels, indicating that corruption in local governments is better understood as a systemic governance issue rather than the outcome of isolated financial performance indicators or audit results.